Tinjauan Supervisi Terhadap Kualitas Pendidikan Di Madrasah Ibtidaiyah Negeri 4 Bireuen - Jaya Sutisna, Ade; Yusrianti, Susi (Indonesian Journal of Islamic Educational Management, 2025)
Supervision plays an important role in improving the quality of education in educational institutions, including madrasahs. This study aims to evaluate the role of supervision in enhancing the quality of education at Madrasah Ibtidaiyah Negeri 4 Bireuen, to identify challenges in its implementation, and to provide recommendations for increasing supervision effectiveness. This research employs a descriptive qualitative approach. Primary data were collected through interviews with the principal and teachers of Madrasah Ibtidaiyah Negeri 4 Bireuen, while secondary data were obtained from relevant literature. The findings indicate that supervision plays a crucial role in improving the quality of education in the madrasah. However, several challenges were identified, including difficulties in translating feedback into concrete actions and a lack of time for reflection and preparation. Recommendations for improving supervision effectiveness include developing a more collaborative approach, allocating more time for reflection and preparation, and enhancing communication and clarity regarding expectations and evaluation criteria